Comprehensive characterization of the structure and properties of human stratum corneum relating to barrier function and skin hydration: modulation by a moisturizer formulation. Issue 9 (3rd April 2021) - Galliano, Marie‐Florence; Tfayli, Ali; Dauskardt, Reinhold H.; Payre, Bruno; Carrasco, Cedric; Bessou‐Touya, Sandrine; Baillet‐Guffroy, Arlette; Duplan, Hélène
Abstract: The stratum corneum (SC) is key in the maintenance of the biomechanical barrier and hydration of skin. Our previous investigations showed beneficial effects of a combination of emollients on water capture and retention and protein and lipid organization, all of which are linked to dryness and dry skin damage. Here, we show how a formulation containing an emollient combination ("Trio") and its basal formulation (placebo) impacted the descriptors of SC hydration in SC layers. Only the Trio formulation—not its placebo formulation—modified SC biomechanical drying stress behaviour and imparted a high capacity to protect it from dehydration. This was in accordance with findings at the molecular level using Raman analyses and at the structural level using cryo‐scanning electron microscopy (SEM). After topical application, only the Trio formulation profoundly increased lateral packing of lipids and their compactness. Cryo‐SEM showed that, unlike the placebo formulation, the Trio formulation prevented the water loss when applied before the dehydration process. In conclusion, these studies demonstrate that stresses in the SC due to dehydration can be alleviated using a formulation containing emollients that interact with the SC lipid components.